Biogenic amine content of Turkish soudjouc (sucuk) samples - Ayhan, Kamuran (Ciencia)
In this study, biogenic amines in Turkish soudjouck samples purchased from markets in Ankara were determined by using HPLC. All the samples have been contained considerable levels of some biogenic amines. The concentration of biogenic amine of the samples fluctuated greatly. Tyramine (TYR), putrescine (PUT) and spermidine (SPD) were the predominant biogenic amines. Tyramine was present in 11 samples, which were 64.70%, and PUT and SPD 52.94%, 41.17% respectively. Although there are no legal limits for the values of biogenic amines, in some samples higher values were found than suggested limits. The highest level of cadaverine was detected in one sample with 514.24 mg/kg and TYR was with 198.14 mg/kg in another one. In addition, microbiological counts of APC, LAB, Enterobacteriaceae, Enterococci, Staphylococci and Yeasts were varied greatly among the samples. The numbers of viable aerobic bacteria (APC) are differed from 3.98 log CFU/g- 7.89 log CFU/g. The count of Lactic acid bacteria (LAB) were found very low level such as 2.45 log CFU/g and 2.79 log CFU/g in some samples.